TECHNOLOGIES FOR FORMING COMMUNICATIVE COMPETENCES OF FUTURE ENGLISH LANGUAGE TEACHERS IN DIGITAL EDUCATION CONDITIONS - Ayjan Anarbekova (European Science Publishing, 2024)
The article talks about the technologies of formation of communicative competences of future English language teachers in the context of digital education.
Keywords: digital, education, environment, English language, teachers, communicative, competence, technology.